INSTALANSI LAMPU PENERANGAN BALAI DESA KARANG ASEM KECAMATAN PALIYAN KABUPATEN GUNUNG KIDUL - Ahsan, Ahmad Nur; Muchammad Hifni (PPM Sdirjianbang Akademi Militer, 2023)
Abstract Karang Asem Village Hall is the only place for Karang Asem Village residents to gather in participating in social activities in the form of counseling or socialization of new things to be conveyed to the surrounding community. Given the importance of the use of the Karang Asem Village Hall in organizing events, it is necessary to have an adequate electrical installation so that there are no obstacles in the continuity of the event. But in reality there is still less or limited lighting around the Karang Asem Village Hall. So that when at night, the village hall looks dark. Furthermore, lecturers and students of the Military Academy's defense electronics engineering study program conducted community service activities in Karang Asem Village by implementing a lighting installation program around the village hall. Keywords: Village Hall, electrical installation, lighting lamp. Abstrak Balai Desa Karang Asem merupakan satu-satunya tempat untuk berkumpul warga Desa Karang Asem dalam mengikuti kegiatan-kegitan sosial baik berupa penyuluhan-penyuluhan ataupun soialisasi hal-hal yang baru untuk disampaikan kepada masyarakat sekitar. Mengingat pentinya kegunaan Balai Desa Karang Asem tersebut dalam penyelenggaraan kegiatan maka diperlukan adanya instalasi kelistrikan yang cukup memadai agar dalam keberlangsungan acara tidak terjadi hambatan. Namun kenyataanya masih kurang atau keterbatasan penerangan pada sekitar Balai Desa Karang Asem. Sehingga apabila pada waktu malam hari, balai desa tampak gelap. Selanjutnya dosen dan mahasiswa prodi teknik elektronika pertahanan Akademi Militer melakukan kegiatan pengabdian kepada Masyarakat di Desa Karang Asem dengan melaksanakan program instalasi lampu penerangan di sekitar balai desa. Kata Kunci: Balai Desa, Insatalasi Listrik, Lampu penerangan